If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-13) = 37 Multiply -1 * -13 x + 13 = 37 Reorder the terms: 13 + x = 37 Solving 13 + x = 37 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = 37 + -13 Combine like terms: 13 + -13 = 0 0 + x = 37 + -13 x = 37 + -13 Combine like terms: 37 + -13 = 24 x = 24 Simplifying x = 24
| 8u-6-15u+26= | | 7y-10+2y-5=-6 | | 12x-4=44 | | -2(x-4)=5x-13 | | 4x-5=21 | | 2x+6-x=15 | | 28-4=44 | | 6n^2+18n-168=0 | | 2x-3=1x+4 | | 10c-9c+1=1 | | -4(r-10)= | | 7m-2=12 | | .33y-2=4 | | 11y-1=21 | | 7x-6x-10=13 | | 15x-241=5x-11 | | 0=t-1.4 | | -2=3n-20-5n | | 3t-7=6t | | 3-y=-39 | | 50+7n= | | 142-5x=40x+17 | | 3m+7=13 | | 8(7x-4)=80 | | x^2+2x-37=0 | | y=2-3x | | -3y=55 | | 2x+4y=56 | | 5x^2+10x-20=0 | | -15x+120=15x | | x^2-4+xy-2y=0 | | y-2y-3= |